2022
DOI: 10.34133/2022/9790320
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Photothermally Enhanced Photocatalytic U(VI) Extraction by a Step-Scheme Heterojunction

Abstract: In this work, a CdS/BiVO4 step-scheme (S-scheme) heterojunction with self-photothermally enhanced photocatalytic effect was synthesized and applied for efficient U(VI) photoextraction. Characterizations such as transient absorption spectroscopy and Tafel test together confirmed the formation of S-scheme heterojunctions, which allows CdS/BiVO4 to avoid photocorrosion while retaining the strong reducing capacity of CdS and the oxidizing capacity of BiVO4. Experimental results such as radical quenching experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The XPS complete spectrum in Figure g demonstrates that there are unmistakably U 4f peaks following the photocatalyst. Also, from the XPS fine spectra of uranium after the reaction (Figure h), it can be seen that the binding energies of 381.3 and 392.3 eV are the characteristic peaks of U(VI), and, notably, the binding energies of 380.6 and 390.1 eV correspond to the characteristic peaks of U(IV), indicating that OVs-BiOBr-30 successfully reduced U(VI) to U(IV) after 60 min of piezoelectric–photocatalysis. The Raman spectroscopy of the reaction OVs-BiOBr-30 (Figure i) revealed that it has a weak characteristic peak at a wavelength of 821 cm –1 , which is associated with uranium peroxide dihydrate [(UO 2 )O 2 ·2H 2 O].…”
Section: Resultsmentioning
confidence: 95%
“…The XPS complete spectrum in Figure g demonstrates that there are unmistakably U 4f peaks following the photocatalyst. Also, from the XPS fine spectra of uranium after the reaction (Figure h), it can be seen that the binding energies of 381.3 and 392.3 eV are the characteristic peaks of U(VI), and, notably, the binding energies of 380.6 and 390.1 eV correspond to the characteristic peaks of U(IV), indicating that OVs-BiOBr-30 successfully reduced U(VI) to U(IV) after 60 min of piezoelectric–photocatalysis. The Raman spectroscopy of the reaction OVs-BiOBr-30 (Figure i) revealed that it has a weak characteristic peak at a wavelength of 821 cm –1 , which is associated with uranium peroxide dihydrate [(UO 2 )O 2 ·2H 2 O].…”
Section: Resultsmentioning
confidence: 95%
“…Both temperature‐dependent catalysts fall within the category of thermal catalysts and may be superior to one another under certain circumstances. The degradation of water contaminants, air purification, water disinfection, and water splitting for hydrogen production and carbon dioxide abatement are some of the potential applications that have been thought of thus far [135,138,139] . In this section, we discuss the mechanisms of thermocatalysis and pyrocatalysis with their potential applications.…”
Section: Types Of Non‐photoresponsive Catalystsmentioning
confidence: 99%
“…Under alternating magnetic field, the piezocatalytic materials could produce ·OH, ·O 2 – , etc., which are active to reduce U­(VI) to solid U­(IV). Zhang et al found that U­(VI) could be reduced to form UO 2 (OH) 2 precipitates by ·OH and ·O 2 – radicals. Because the magnetic field was easily obtained, the piezocatalytic elimination of U­(VI) or other metals could be achieved easily.…”
Section: Other Techniquesmentioning
confidence: 99%